USING “UNSTOPPABLE” SONG TO INCREASE MEDICAL RECORD STUDENTS’ SIMPLE PRESENT TENSE MASTERY AT STIKES WIDYA DHARMA HUSADA TANGERANG - Dony Mahendra (Cakrawala Pedagogik, 2023)
The goal of the study was to determine the effectiveness of using the "Unstoppable" song to increase the medical record students' mastery on simple present tense at STIKes Widya Dharma Husada Tangerang. Lack of attractive media and students' proficiency with the simple present tense in spoken and written language were the problems. The methodology used was a class action research study of the Kemmis and Mc Taggart design with two cycles. The model included was planning, action, observation, and reflection. The respondents were 36 students of first semester in medical record at STIKes Widya Dharma Husada Tangerang. The outcomes demonstrated that employing this medium resulted in a significant improvement. It appears as follows, in the first cycle, the original condition of 60.92 was raised to 71.44; in the second cycle, 71.44 was raised to 84.19. To sum up, teaching the students of medical record with "Unstoppable" song could be an effective way to help them become more proficient with the simple present tense.